Surface Plasmon-Polariton: A Novel Way To Initiate Azide-Alkyne Cycloaddition - Guselnikova, Olga; Postnikov, Pavel; Chehimi, Mohamed M; Kalachyovaa, Yevgeniya; Svorcik, Vaclav; Lyutakov, Oleksiy (Langmuir, 2019)
Plasmon catalysis has recently generated tremendous interest in the field of modern chemistry. Application of plasmon introduces the principally new stimulus for the activation of organic reactions, keeping the optical energy concentrated in the vicinity of plasmonic structure, creating an optical near-field enhancement as well as hot electron injection. In this work, for the first time, we presented a new way for the initiation of the azide-alkyne cycloaddition (AAC) using the surface plasmon-polariton wave, supported by the gold grating. With this concept in hand, the plasmon-active gold grating was functionalized with 4-ethynylbenzenediazonium compound. Then, surface-grafted 4-ethynylphenyl groups were plasmon activated and clicked with 4-azidobenzoic acid. Additional experiments allowed to exclude the potential effect of photon, heating, and metal impurities confirmed the key role of surface plasmon-polariton AAC activation. For the investigation of plasmon-induced AAC mechanism, 4-azidophenyl groups (instead of 4-ethynylphenyl groups) were also grafted to the grating surface. Further careful evaluation of reaction kinetics demonstrates that the AAC reaction rate is significantly higher in the case of acetylene activation than in the case of azide activation.